Naprężenia momentowe w termosprężystości - Nowacki, W. (Engineering Transactions, 1968)
The aim of the present paper is to generalize some theorems on the coupled thermoelasticity on a medium characterised by two vectors independent from each other: the displacement vector u and the rotation vector ω.Basing on the thermodynamics of irreversible processes the constitutive equations and the expanded equation of heat conductivity for an isotropic medium are derived. The author succeeded in obtaining a basic system of differential equations of coupled thermoelasticity. The propagationof thermoelastic waves in an unbounded medium is discussed. Moreover, a generalization of the virtual work principle on dynamic problem of coupled thermoelasticity is advanced. Finally, the reciprocity theorem is derived and some conclusions resulting from this theorem are discussed.